A Practical Circuit of Cyclic Chirp Spread Spectrum Modulation for Long Range Communication - Ananta Sinchai; Nopparut Sae-Lim; Chotipat Pornavalai; Paramote Wardkein; Panwit Tuwanut (2022 37th International Technical Conference on Circuits/Systems, Computers and Communications (ITC-CSCC), 2022)
Various technologies have been utilized in long range communication to satisfy increasing usage of the internet of things in a wide large area. Recently, a modulating technique called cyclic chirp spread spectrum (CSS) modulation has attracted attention due to its low power usage and long-range coverage. However, a cyclic CSS circuit is complex to build. Hence, the objective of the work is to propose a practical circuit of cyclic CSS modulation. The proposed circuit is designed to complicated-free creation. To prove that the presented circuit is pragmatic, a simulation test is performed. The simulation results have illustrated that the designed circuit well generates a chirp modulating signal. Also, the proposed circuit is flexibly configurable.
Keywords: IoT Networks and Protocols; Bluetooth and Wireless Communication Technologies; Underwater Vehicles and Communication Systems